Topikalisasi Struktur Teks Dan Genre Wacana Pada Artikel Opini Dalam Koran Kompas Serta ImplementasinyaDalam Pembelajaran Bahasa Indonesia - Hikmawati, Ahfi; , Drs. Agus Budi Wahyudi, M.Hum (2016)
In analysing this opinion the writer tends to use the viewpoint of each other. It is caused the knowledge and the way writer thinks is different. So that, in opinion articles can be useful if the topicalitation and discourse genre in Kompas's newspaper on July's edition 2015 are investigated and its implementation in learning indonesian in Senior High School's level. The aims of this study is to explain the form of topicalitation of text structure , to describe discourse genre and to explain the implementation of topicalitation of text structure and discourse genre of opinion articles in Kompas's Newspaper in learning Indonesian. The method used listening technique and record technique to collect the data. To make the data valid, the writer used triangulation theory. Triangulation theory is used to compare the data with the existing theories. The distribution method is used to analyze the data. The results of this study are topicalitation of text structure, discourse genre, and its implementation. In topicalitation of text structure there are some scopes the found topic of political administration, economic, law and justice, the politic of the local elections, social-community, religion and culture. In this study, the found discourse genres: reports genre of opinion articles, exposition genre, description genre, explanation genre and discussion genre. The implementation of the study is used to learning process that is based on the topicalitation text structure and discourse genre in Kompas's newspaper. The result of topicalitation of text structure are applied in learning Indonesian material the opinion texts at 12th grade, report texts are applied in learning Indonesian at 10th grade, exposition texts are applied applied in learning Indonesian at 10th grade, and explanation texts are applied in learning Indonesian at 9th grade. Keyword: discourse genre, implementation, and topicalization.